THE IMPACT OF USING SHOPEE PAYLATER PAYMENTS ON THE CONSUMER BEHAVIOR OF KUPANG CITY SOCIETY - Fajrin, Fauziah Amalia; Tiwu, Maria Indriyani Hewe; Kiak, Novi Theresia (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
Things that influence related with behavior consumptive is demands social and environmental place Where individual That life . In addition , the style life is also one of influential thing to the emergence need desire as well as behavior in buy something . So from That Behavior consumptive is behavior consume the real stuff not enough or No necessary ( especially those related to with response to consumption goods secondary , namely items that are not too required ). The method to be used done in study This is questionnaire or questionnaire . Questionnaire or questionnaire is a set question or statement that must be answered by respondents . Research This use instrument Use of Shopee Paylater and behavior consumptive . Questionnaire in study This use scale likert scale Likert is the scale used For measure attitudes , opinions and perceptions somebody or group of people about social phenomena . From the results study show that majority Respondent payment system users shopee paylater is Woman with amount by 78% or 78 people and men a total of 22% or 22 communities . After analyze all over results obtained from each variables , hypothesis testing is carried out with using SPSS (Statistical Product and Service Solution) version 26 for test the hypothesis proposed in study that is is there any influence use system payment shopee paylater to behavior consumptive among public city Kupang or no . Based on results testing show that variable system payment shopee paylater influential significant to behavior consumptive.